The promotor polymorphism of macrophage metalloelastase in multiple sclerosis - Hladíková, Magdaléna; Štourač, Pavel; Benešová, Yvonne; Tschöplová, Svatava (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2009)
Multiple sclerosis is a chronic demyelinating disease of the central nervous system in which the genetic background plays an important role. Its pathophysiology is characterised by two major processes: neuroinflammation and neurodegeneration. Matrix metalloproteinases are involved in both of them. Macrophage metalloelastase is one of the three matrix metalloproteinases the common elevation of which has been confirmed in multiple sclerosis and also in animal models with experimental allergic encephalomyelitis. To assess the association between its promotor polymorphism and demyelinating disease we genotyped a total of 92 patients (23 men, 69 women, mean age 37 years) with definite multiple sclerosis (according to the McDonald criteria) and 51 healthy controls (17 men, 34 women) matched for age and sex. Genotyping was performed by means of polymerase chain reaction with restriction analysis. We observed no statistically significant differences in genotype or allele distribution of –82 A/G polymorphism between the groups examined (OR=2.6, p=0.026, pcorr=0.078). Due to insufficient numbers of patients with the progressive form [9], no statistically significant differences in genotype or allele frequencies emerged among the patients with variant forms of multiple sclerosis. Nevertheless, all patients with the progressive form (which is associated with a more severe course and higher disability) were of the same genotype: homozygotes AA. This genotype is connected with higher promotor activity and a higher expression of the final protein. It may represent a variant genotype base for a different course of multiple sclerosis in the polymorphism under investigation.
Keywords: financování organizované; genetické techniky; Statistics as Topic; Genotype; statistika jako téma; polymerázová řetězová reakce; Polymerase Chain Reaction; Genetic Research; lidé; Multiple Sclerosis; genotyp; roztroušená skleróza; studie případů a kontrol; Financing, Organized; Case-Control Studies; genetický výzkum; polymorfismus genetický; Matrix Metalloproteinase 12; Genetic Techniques; Polymorphism, Genetic; matrixová metaloproteinasa 12; Humans